Evaluasi Penyediaan Fasilitas Wisata Museum Geologi Menuju Museum Ramah Disabilitas - Nuzul Putri Deliani; Astri Mutia Ekasari (UNISBA Press, 2023)
Abstract. Persons with disabilities must have easy access, treatment and adequate accommodation to meet their needs as tourists as well as equality and opportunity to carry out tourism activities. The Geology Museum is the first museum in the city of Bandung to declare it friendly for visitors with disabilities in 2019. In creating a friendly museum for visitors with disabilities, the provision of tourist facilities at the Geology Museum needs to be a concern. The purpose of this research is to identify the achievements of the Geology Museum in providing tourism facilities to disability-friendly museums. This type of research was carried out qualitatively, with a formal evaluation approach method through collecting data from literature studies and observations which were processed by comparative analysis. The evaluation instrument refers to Permen PU No. 30 of 2006, Bandung City Regional Regulation No. 15 of 2019, and City of Toronto Accessibility Design Guidelines (2004). The results of this study note that only 58% of the facilities available at the Geology Museum are said to be sufficient to go to a disability-friendly museum. Abstrak. Penyandang disabilitas harus memiliki akses yang memudahkan, mendapatkan perlakuan, dan akomodasi yang layak untuk memenuhi kebutuhan mereka sebagai wisatawan serta kesetaraan dan kesempatan untuk melakukan kegiatan wisata. Museum Geologi menjadi museum pertama di Kota Bandung yang mencanangkan ramah bagi pengunjung disabilitas pada tahun 2019. Dalam mewujudkan museum ramah bagi pengunjung disabilitas, penyediaan fasilitas wisata di Museum Geologi perlu menjadi perhatian. Tujuan penelitian ini untuk mengidentifikasi capaian Museum Geologi dalam penyediaan fasilitas wisata menuju museum ramah disabilitas. Jenis penelitian dilakukan secara kualitatif, dengan metode pendekatan evaluasi formal melalui pengumpulan data studi literatur dan observasi yang diolah dengan analisis komparatif. Intrumen evaluasi mengacu pada Permen PU No.30 Tahun 2006, Perda Kota Bandung No.15 Tahun 2019, dan City of Toronto Accessibility Design Guidelines (2004). Hasil dari penelitian ini diketahui bahwa hanya 58% fasilitas yang tersedia di Museum Geologi dikatakan cukup untuk menuju museum ramah disabilitas.